Identification of key phenolic compounds responsible for antioxidant activities of free and bound fractions of blackberry varieties' extracts by boosted regression trees. (14th August 2021) - Gong, Er Sheng; Li, Bin; Li, Binxu; Podio, Natalia S; Chen, Hongyu; Li, Tong; Sun, Xiyun; Gao, Ningxuan; Wu, Wenlong; Yang, Tianran; Xin, Guang; Tian, Jinlong; et al.
Abstract: BACKGROUND: Free fractions of different blackberry varieties' extracts are high in phenolic compounds with antioxidant activities. However, the phenolic profiles and antioxidant activities against peroxyl radicals of bound fractions of different blackberry varieties' extracts have not been previously reported. In addition, what the key antioxidant phenolic compounds are in free and bound fractions of blackberry extracts remain unknown. This study aimed to investigate the phenolic profiles and antioxidant activities of free and bound fractions of eight blackberry varieties' extracts and reveal the key antioxidant phenolic compounds by boosted regression trees. RESULTS: Fifteen phenolics (three anthocyanins, four flavonols, three phenolic acids, two proanthocyanidins, and three ellagitannins) were identified in blackberry by ultra‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. Ferulic acid, ellagic acid, procyanidin C1, kaempferol‐ O ‐hexoside, ellagitannins hex, and gallic acid were major bound phenolics. Bound fractions of eight blackberry varieties' extracts were high in phenolics and showed great antioxidant activity. Boosted regression trees analysis showed that cyanidin‐3‐ O ‐glucoside and chlorogenic acid were the most significant compounds, contributing 48.4% and 15.9% respectively to the antioxidant activity of free fraction. Ferulic acid was the most significant antioxidant compound in bound fraction, with a contribution of 61.5%. Principal component analysis showed that Kiowa was the best among the eight varieties due to its phenolic profile and antioxidant activity. CONCLUSION: It was concluded that blackberry varieties contained high amounts of bound phenolics, which confer health benefits through reducing oxidative stress. Ferulic acid was the key compound to explain the antioxidant activities of bound fractions. © 2021 Society of Chemical Industry.